Report on business attachment with Reinsurance management corporation of Asia (Pte) Ltd. - Ng, Chui Nee. (2009)
The main purpose of this report is to give an insight to the training experience gained by the student in Reinsurance Management Corporation Of Asia (pte) Ltd under the Business Attachment Programme.